Tolerance and accumulation of cesium and strontium in saprothophic fungi. (April 2015) - Seeprasert, P; Yoneda, M; Shimada, Y; Matsui, Y
Abstract: Soil contamination by nuclear accidents has led to a resurgence of interest in microbe-radionuclide interactions. Soil fungi accumulate radioactive elements from contaminated soil, and it has been hypothesized that this may alter the availability of radionuclides to plants and alter their movement in particular areas. This study intended to demonstrate how soil saprotrophic fungi accumulated Cs and Sr isotopes in both stable and radioactive solution forms. An experiment to determine the tolerance of fungal growth under extremely inhibitory concentrations of Cs and Sr stable isotopes was conducted. The results showed that fungal cells were more sensitive to Cs than to Sr. Accumulations of Cs and Sr were examined through sorption mechanisms using resting cells in the solutions under various conditions. The sorption capacity was indirectly determined by analysing the elements, which decreased in the solution. The equilibrium data were fitted with sorption isotherms to show the best fit with the Langmuir isotherm for both elements, assuming that the sorption sites form a surface monolayer. In addition, pH was examined to investigate its effect on the sorption capacity of Cs and Sr.